Effect of maternal zinc supplementation or zinc status on pregnancy complications and perinatal outcomes: An umbrella review of meta-analyses - Iqbal, Sehar (Heliyon, 2021)
Zinc is an essential trace element involved in different physiological functions. During pregnancy, it plays a crucial role in healthy embryogenesis. This umbrella review, therefore, aimed to summarize the existing literature of meta-analyses evaluating the effect of maternal zinc supplementation or zinc status on maternal and neonatal outcomes. Two databases, PubMed and Scopus, were selected to search the available literature without any temporal restriction. The literature search was performed during October 2020 and a total of 192 records were identified through the literature search. After screening the titles and applying the inclusion/exclusion criteria, finally, 15 articles were included in this umbrella review. This umbrella review showed that maternal zinc supplements reduce the risk of preterm birth. Although no substantial effect of zinc supplements was found for other feto-maternal outcomes. Also, we found a significant relationship between low maternal zinc status and risk of pregnancy complications. Zinc supplements reduce the risk of preterm birth. Long-term interventions and cohort studies are needed for future research directions. Further studies and a thorough investigation will help to decide the recommended zinc dose or intake during pregnancy.